(3GdQjGVjGJ GdbOjeI (B:s (3hfXQjI GdYde GdadSajI (B/s - (3GdeQRhbj, CHh jYQHs ((3JhfS (B:s (3GdOGQ GdJhfSjI ddfTQ ,s, 1985)
(3jdGMX ef NdGd gPg GdfeGPL ef GdbVGjG GdJj jWQMgG cJGH GdQjGVjGJ GdbOjeI h fXQjI GdYde GdadSajI aGf GdeDda bO eRL Hjf GdJGQjN h GdYde h GdadSaI eRLG LOjQG HGdJfhjg h dFf cGfJ GQGDg h GSJfJGLGJg eOYGI Gdi GdfbO h GdJbjje ef bHd Ggd GdGNJUGU adjJGcO GdbGQF Gfg HGRGA cJGH eajO h eG Pdc HGdfYJ Gdgjf s
Keywords: (3adSaIs; (3GdQjGVjGJs; (3Ydes